(untitled) (Raparin Journal of Humanities (RJH), 2020)
The issue of writing history by Kurdish authors in Iraq between1958-1968 is analysed and explained which is about those printed books in kurdish written and published by Kurdish authors in Iraq. We have concluded that eight history books were published in Kurdish language from 1958 to 1968. Among them, seven of them were written and published from 1958 to 1962 and only one book was published in 1968. This devision of publishing those books has been due to politicial reasons and the emergence of Ailul revolution in 1961. On the one hand, it was due to the political unrest which was a stumbling block for the writing process for authors. On the other hand, however, it was due to the Aylul revolution that led to the restriction of the writing and publication processes by the Iraqi government. The historeans were peoples of different backgrounds in Kurdistan including politicians, army, religious people, school teachers, poets, and scholars. This show the desire of writing history by peoples of different backgrounds in the Kurdish society. Regarding the academic and scientific quality and the methodology of adopted at that time in writing history books, although it cannot be compared by today’s history books, but it was rather narrative and simple. In addition, very few references were usually used in writing those books. This was due to the fact that the history books authors were not historians.